Introducing the New PPB - Pragmatic Program Budgeting : Overcoming Design Obstacles to Planning, Management, and Control - Brumby, James; Hashim, Ali; Piatti Fuenfkirchen, Moritz (World Bank, Washington, DC, 2022)
Program budgeting is a reform that intends to shift the focus of budgetary processes from control of inputs to producing measurable results. It aspires to enable governments deploy resources to priority areas and assess whether the resources have been translated into intended results. This paper identifies specific stumbling blocks for countries already implementing program budgeting that have caused implementation difficulties, especially in budget execution, and suggests means to resolve them. This paper aims to help resolve the tensions between planning, management, and control in pursuit of higher performance from governments. In doing so, the focus is not only observing and supporting the efficiency and effectiveness goals of program budgeting but also resolving the tensions arising from execution control and designing measures to support analysis and performance